Anticonvulsant Activity of 2-(Substituted-imino)thiazolidin-4-ones - Gong, G.-H.; Wang, D.; Zhang, J.-F.; Wei, C.-X.; Quan, Z.-S. (Drug Research, 2014)
A novel series of 2-(substituted-imino)thiazolidin-4-ones were synthesized and evaluated for anticonvulsant activity using the maximal electroshock seizure (MES) and subcutaneous pentylenetetrazole (Sc-PTZ) assays and their neurotoxicity was measured by the rotarod test. The results of these tests demonstrated that 2-(4-(pentyloxy)phenylimino)thiazolidin-4-one (5d) was the most potent anticonvulsant, with ED50 value of 18.5 mg/kg and 15.3 mg/kg in the MES and Sc-PTZ tests, and protective index (PI=TD50/ED50) values of 10.6 and 12.8 respectively. 5d was much safer than a reference drug Carbamazepine.
Keywords: thiazolidin-4-one; anticonvulsant; MES; Sc-PTZ; neurotoxicity